The relationship between hope and happiness with prenatal care - Elham Sadat Hoseini; Raziyeh Rahmati; Fatemeh Shaghaghi; Marjan Beigi; Zahra Mohebbi-Dehnavi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Prenatal care refers to proper and principled implementation aimed at maintaining a healthy pregnancy in terms of physical health and favorable psychological outcomes for the mother, infant, and family. The adequacy of prenatal care is an important indicator in predicting infant and maternal mortality. Mental health components such as hope and happiness can influence the quality of prenatal care. The aim of this study was to determine the relationship between hope and happiness with prenatal care. METHODS: This is a cross-sectional study that was performed on 200 pregnant mothers referred to Isfahan, Iran, comprehensive health centers in 2018 using an available sampling method. The research instrument was a questionnaire of hope, happiness, and quality of prenatal care that was completed by qualified people. The data were analyzed by descriptive and analytical statistical methods (Pearson correlation). RESULTS: The results of this study showed that there is a significant relationship between the adequacy of care and overall hope score (P = 0.032). There was also a positive and significant relationship between the adequacy of care and the subscales of hope (thinking [P = 0.002] and path [P = 0.004]). There was a positive and significant relationship between the adequacy of prenatal care and overall happiness score (P = 0.03). Positive emotion subscale (P = 0.033) had a significant positive correlation and negative emotion subscale (P = 0.001) had a significant negative relationship with the adequacy of prenatal care. CONCLUSION: According to the results, mental health can affect the quality of prenatal care. As a result, health providers to pregnant mothers can improve the adequacy of prenatal care by examining pregnant women in terms of these two issues, thereby improving the health of themselves and their children, and ultimately, community health.